Primary splenic abscess in children - Abimbola Abiola; Shehu Hassan; Emmanuel A. Ameh (Elsevier, 2020)
Primary splenic abscess in children is frequently missed due to the predominance of non-specific symptoms.A 7 year old girl presented with fever, vomiting, abdominal pain and diarrhea and there was mild generalised abdominal tenderness most marked in the left hypochondrium. Ultrasonography and computed tomography scan showed an enlarged spleen with a mixed density collection at the lower pole considered to be a splenic abscess. Intravenous broad spectrum antibiotics were commenced. Laparotomy confirmed a splenic abscess in the lower pole necessitating a partial splenectomy. Postoperative course was uneventful and the patient has remained well at 2 years of follow up. Streptococcus was cultured from the pus and histology confirmed splenic abscess in a healthy spleen. The literature on primary splenic abscess in children has been briefly reviewed for raised awareness and to facilitate early diagnosis and treatment.